Postpartum women's perception of early discharge from hospital - Rapinyana, Ogar (My University, 2014)
The purpose of the study was to investigate womens’ perceptions of early discharge after childbirth and to determine their needs. The study aims to create an awareness that could lead to improved service and meet the needs of postnatal women. The study was conducted in Francistown, Botswana. A descriptive survey design was used in order to study the views of postpartum mothers in relation to early postpartum discharge. The target population was postnatal mothers six weeks post-delivery. Simple random sampling was used to select five clinics for the study. Convenience sampling was used to select a sample of at least 22 postnatal women from each clinic. A sample of 110 postnatal women was obtained from five clinics. A structured interview schedule was used and both open and close-ended questions were utilised. The findings of the study revealed that respondents felt that it was good to be discharged early in order to join their families at home for support. Those respondents who felt it was not good, felt that they lacked information and basic skills in relation to care of their babies and self. The findings further showed that primiparae experienced stressful events post-delivery for example, tearfulness. The limitations are that the study was conducted in only one urban setting, therefore the findings cannot be generalised beyond the sample. The findings of this research are also limited to the five clinics. It is recommended that each postnatal ward should have a teaching manual which provides instruction or information that must be given by the midwives to the postnatal women. It is also recommended that the needs of the mothers be recognised, so that information given is individualised. The researcher goes on to recommend that a similar study should be conducted on teenage mothers to identify problems of groups with special needs.